Paulo Freire's pedagogy and Marxism: political education in Via Campesina Brazil: Pedagogia freireana e marxismo: a formação política na Via Campesina Brasil - Perruso, Marco Antonio (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2017)
This article discusses processes of political education in Via Campesina Brazil, whose movements in recent years have dealt remarkably with the themes of youth and education. For analytical purposes, I present two ideal types of political education: one refers to the old communist hegemony in our social movements, while the other refers to the influence of Liberation Theology and Marxist dissident sectors from the 1970s. From the analysis of documents collected and interviews, as well as the relevant literature, I conclude that there exists a greater connection between the political education of Via Campesina Brazil and the second ideal type.